1995
DOI: 10.1080/15287399509532038
|View full text |Cite
|
Sign up to set email alerts
|

Ketone potentiation of haloalkane‐induced hepato‐ and nephrotoxicity. II. implication of monooxygenases

Abstract: Previous results in Sprague-Dawley rats indicate that acetone (A), methyl ethyl ketone (MEK), and methyl isobutyl ketone (MiBK) pretreatment (3 d, po) at dosages of 6.8 and 13.6 mmol/kg potentiate CCl4 hepatotoxicity and CHCl3 nephrotoxicity, respectively. The potentiation potency profile observed was MiBK > A > MEK for liver and A > MEK > or = MiBK for kidney toxicity (Raymond & Plaa, 1995). In the present study, hepatic and renal microsomes from A-, MEK-, and MiBK-pretreated rats (6.8 or 13.6 mmol/kg) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…These two compounds are known inductors of the isoform 2E1 of the CYP 450 [8,9,19]. Chloroform nephrotoxicity is enhanced by pretreatment with acetone [20]. The possibility that the increased toxicity of xenobiotics in animals exposed translactionally to ethanol was due to induction of CYP 450 2E1 was suggested by Chhabra et al [21] in Sprague-Dawley rats.…”
Section: Discussionmentioning
confidence: 99%
“…These two compounds are known inductors of the isoform 2E1 of the CYP 450 [8,9,19]. Chloroform nephrotoxicity is enhanced by pretreatment with acetone [20]. The possibility that the increased toxicity of xenobiotics in animals exposed translactionally to ethanol was due to induction of CYP 450 2E1 was suggested by Chhabra et al [21] in Sprague-Dawley rats.…”
Section: Discussionmentioning
confidence: 99%
“…The letter metabolite was not detected with oral administration [ 852 , 854 ]. MIBK has been shown to induce liver and renal CYPs, potentiating hepato- and nephrotoxicity produced by chloroform and carbon tetrachloride [ 853 , 855 , 856 ].…”
Section: Epigenetic Carcinogens or Carcinogens With Uncertain Mode Of...mentioning
confidence: 99%
“…MoA underlying hepatocarcinogenicity of MIBK in mice is not well understood. While it potentiated hepatotoxicity and cholestasis produced by other chemicals [ 853 , 855 , 856 , 859 , 860 ] no evidence of hepatotoxicity was observed when MIBK was administered alone [ 275 , 843 ]. A study by Hughes and colleagues [ 861 ] suggested involvement of receptor-mediated mechanism, specifically, activation of the CAR/PXR nuclear receptors, which results in hepatocellular proliferation consequently leading to tumor development.…”
Section: Epigenetic Carcinogens or Carcinogens With Uncertain Mode Of...mentioning
confidence: 99%
“…According to Raymond and Plaa (1995a), the oral administration to male rats of 1362 mg/kg MIBK in 5% polyoxyethylated castor oil produced increased renal cytochrome P-450 and aniline hydroxylase activity and increased liver and renal aminopyrine N-demethylase activity. No histopathology was noted.…”
Section: Effect On Enzyme Activitymentioning
confidence: 99%